Silage bales An emerging enterprise - Singh, Ajitpal; Singh, Sarvpriya; Singh, Palwinder (Indian Farming, 2024)
This success story is based on silage unit of Sh. Kulwinder Singh who started selling silage along with dairy business and established a new milestone of success.